Tendances démographiques et impact économique - Sirard, André (Assurances)

(untitled) (HEC Montréal, 1989)
Economic growth in most leading industrialized nations is quite strong. The surprising burst of growth we saw in most OECD countries in 1988 led lo a small acceleration in inflation and a round of interest rate increases. However, slower growth is expected over the next 12 months. Inflation will remain modest and interest rates will probably decline.